Sri Lanka Poverty Assessment : Accelerating Economic Transformation - World Bank (World Bank, Washington, DC, 2021)
Sri Lanka has an impressive track record of reducing poverty and sharing prosperity more broadly. A dynamic decade that spurred post-war growth and continued with a process of economic transformation led to a productivity boost and labor reallocation from agriculture to industry and services. The COVID-19 pandemic is expected to have resulted in a significant reversal of welfare gains. Before COVID-19, poverty reduction was mainly driven by increased labor earnings from nonfarm sectors. New jobs were created in these sectors but there are concerns about their quality. Progress in improving agricultural earnings was slow; and the performance of social protection continued to be weak—these trends held back further progress in economic transformation and poverty reduction.